Development of advanced NO[sub x] control concepts for coal-fired utility boilers - Evans, A.; Pont, J. N.; England, G.; Seeker, W. R. (Energy and Environmental Research Corporation, 1992)
All three of the CombiNO[sub x] NO[sub x] control technologies were performed simultaneously for the first time. Tests were performed while firing coal as the primary fuel, and natural gas and coal as reburn fuels. The results for the complete CombiNO[sub x] process for coal firing and natural gas reburning are displayed in Figure 3-1. NO/NO[sub x] measurements were taken with the new sample system. The filter and line were cleaned periodically throughout testing to avoid ash build-up; ash has also been shown to convert NO[sub 2] to NO. Reduction due to natural gas reburning was 54% with burnout air injected at a downstream location of approximately 1600[degree]F. Advanced Gas Reburning produced a 79% reduction -- although it is suspected that better reduction would have been possible if injection resolution in the furnace allowed the urea to be injected at a more optimum temperature of 1850[degree]F. The methanol injection step converted 45% of the existing NO to NO[sub 2], achieving an overall CombiNO[sub x] NO reduction of 89%. The coal reburning CombiNO[sub x] test results are displayed in Figure 3-2. Results are similar to those obtained for natural gas reburning. Reduction due to urea injection was better while reburning with coal than for natural gas, probably due to the more optimum urea injection temperature. The methanol injection step converted 40% of the NO to NO[sub 2], similar to the 45% NO conversion that occurred for natural gas reburning. An overall CombiNO[sub x] NO reduction of 93% was achieved, resulting in a final NO concentration of 61 ppM at 3% O[sub 2].